Analisis Kelayakan Aplikasi BISA (Belajar Islam dan Bahasa Arab) sebagai Media Pembelajaran Bahasa Arab - Resma Dewi Nurpitri (Mahira: Journal of Arabic Studies & Teaching, 2023)
This study aims to determine the feasibility level of the BISA application based on the theory of multimedia learning assessment and to find out the opinions of Arabic language experts about the application as a learning medium. This research is a mixed methods. Collecting data analyzed in this study using the documentation method and to find out the opinions of Arabic language experts the researchers used the questionnaire/questionnaire method. In the data analysis technique, the researcher used descriptive statistical analysis methods. The results of the study stated that the BISA application obtained a score percentage of 69.05% which was interpreted as a fairly decent category. Meanwhile, based on the results of the questionnaire/questionnaire, the BISA application obtained a percentage score of 80% which was categorized as quite feasible. The BISA application as learning multimedia has integrated several forms of media such as text, images, audio, and video. The material in this application already includes knowledge and skills material and contains enrichment material, so that Arabic language experts think that the application is appropriate for novice learners. The lack of application is found in several indicators including indicators of cognitive content, artistic and aesthetic indicators, and indicators of overall function.